Prevalence and risk factors for asymptomatic venous thromboembolism in patients with primary brain tumors - Viktoria Nemecz; Reinhard B. Raggam; Tadeja Urbanic-Purkart; Kujtim Bytyqi; Florian Prüller; Florian Posch; Stefan Hatzl; Sascha Freigang; Stefan Wolfsberger; Marianne Brodmann; Thomas Gary (iScience)
Summary: Patients with primary brain tumors have a high risk of venous thromboembolism (VTE). This study aims to estimate the prevalence of asymptomatic VTE and to identify risk factors and biomarkers for asymptomatic VTE in patients with brain tumors by screening for asymptomatic LE-DVT. Fifty patients were included in the study. Nine patients (18%) experienced a VTE event during the study period. The cumulative 12-month incidence of prospective VTE was 14%. In an exploratory analysis of all VTE events, higher Galectin-3 levels were significantly associated with any VTE event (SOR = 2.35, 95% CI: 1.04–5.34; p = 0.04). According to time-to-VTE regression analyses, higher D-dimer, Galectin-3 levels, and von Willebrand factor activity were predictive of increased VTE risk. This study revealed a high prevalence of asymptomatic LE-DVT in patients with primary brain tumors and found that galectin-3 may be used as a biomarker to identify patients with primary brain tumors at high risk of VTE.